2019
DOI: 10.1007/s11010-019-03511-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury

Abstract: Exosomes are nanometer-sized vesicles involved in intercellular communication, and they are released by various cell types. To learn about exosomes produced by Schwann cells (SCs) and to explore their potential function in repairing the central nervous system (CNS), we isolated exosomes from supernatants of SCs by ultracentrifugation, characterized them by electron microscopy and immunoblotting and determined their protein profile using proteomic analysis. The results demonstrated that Schwann cell-derived exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…Nonetheless, the regulation effect of EVs on PI3K and more pathways should not be confined in shutting miRs, because several defined lncRNAs have been reported to exert neuroprotective potential [60][61][62], and proteins enriched in SC-derived EVs also could act as bioactive factors once delivered to recipient cells, enhancing proliferation and migration as well as angiogenesis, while negatively regulating apoptosis and oxidative stress [63]. Therefore, more potential of SKP-SC-EVs such as axon guidance, pro-angiogenesis, promoting myelination, and immune inflammation modulation for neuroregeneration microenvironment construction should be further investigated, depending on the genetic and proteomic contents.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the regulation effect of EVs on PI3K and more pathways should not be confined in shutting miRs, because several defined lncRNAs have been reported to exert neuroprotective potential [60][61][62], and proteins enriched in SC-derived EVs also could act as bioactive factors once delivered to recipient cells, enhancing proliferation and migration as well as angiogenesis, while negatively regulating apoptosis and oxidative stress [63]. Therefore, more potential of SKP-SC-EVs such as axon guidance, pro-angiogenesis, promoting myelination, and immune inflammation modulation for neuroregeneration microenvironment construction should be further investigated, depending on the genetic and proteomic contents.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we found that rSC exosomes contained miRNAs that are reported to be involved in diverse functions, including cellular adhesion and modulation of immune activities. Furthermore, a recent proteomic analysis of rSC exosomes showed that they contain proteins associated with different biological processes, including cell adhesion, angiogenesis and immune responses (Wei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicate that microRNAs (miRNAs) carried in exosomes from Schwann cells, macrophages and neurons have a significant impact in the processes that underlie peripheral nerve regeneration [ 176 ]. Proteomic analysis of Schwann cell-derived exosomes revealed the presence of several proteins and signaling pathways that are involved in axon regeneration [ 177 ]. Inflammatory cells appear also to promote the emergence of a growth promoting state in the injured neuron through the release of exosomal NADPH oxidase 2 (NOX2) complexes into the injured axons.…”
Section: Evs In Axon Regenerationmentioning
confidence: 99%